Long term results of a phase 2 study of vincristine sulfate liposome injection (Marqibo®) substituted for non‐liposomal vincristine in cyclophosphamide, doxorubicin, vincristine, prednisone with or without rituximab for patients with untreated aggressive non‐Hodgkin lymphomas. (27th June 2013) - Hagemeister, Fredrick; Rodriguez, Maria Alma; Deitcher, Steven R.; Younes, Anas; Fayad, Luis; Goy, Andre; Dang, Nam H.; Forman, Arthur; McLaughlin, Peter; Medeiros, Leonard Jeffrey; Pro, Barbara; Romaguera, Jorge; et al.
Summary Vincristine sulfate liposome injection (VSLI; Marqibo®; M) is active in relapsed and refractory lymphomas, and approved in the United States for relapsed and refractory adult acute lymphocytic leukaemia. We evaluated VSLI (2·0 mg/m2 without dose cap) substituted for non‐liposomal vincristine (VCR) in a cyclophosphamide, doxorubicin, vincristine, prednisone ± ritiximab (CHOP±R) regimen, creating CHMP±R in 72 untreated, aggressive non‐Hodgkin lymphoma patients, including 60 with diffuse large B‐cell lymphoma (DLBCL). The overall response rate was 96% (69/72) including complete response (CR) in 65 (90%) and unconfirmed CR in 2 (3%). Median progression‐free survival (PFS) and overall survival (OS) were not reached at median follow‐up of 8 and 10·2 years, respectively. The 5‐ and 10‐year PFS and OS were 75%, 63%, 87%, and 77%, respectively. Despite VSLI exposure of up to 35 mg, the safety profile of CHMP±R was comparable to that reported for CHOP±R. Grade 3 peripheral neuropathy was reported in 2 (3%) patients; there was no reported Grade 3/4 constipation. CHMP±R was highly active, generally well tolerated, and compared favourably to historical trials with R‐CHOP in DLBCL. This enhanced activity probably reflects VCR dose intensification, pharmacokinetic optimization, and enhanced delivery afforded by VSLI. A Phase 3 trial of R‐CHMP versus R‐CHOP in elderly patients with untreated DLBCL is ongoing.